PENERAPAN METODE VERY LOW FREQUENCY (VLF) PADA LOKASI ANOMALI GEOMAGNETIK RENDAH - Kanata, Bulkis; Zubaidah, Teti; Susanto, Oki Prio (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
The research with title Evaluation of measurement result of geomagnetic anomaly in lombok island, west nusa tenggara and analysis of itâ€™s relation with gravitation anomaly and prediction of local geology (Zubaidah, 2005) in area about 25 x 30 km2 result a isogam map, which known that the minimum geomagnetic anomaly equal to 558,194413 nT located in Seganteng, West Lombok (08035â€™46,2â€ LS, 116008â€™10,9â€ BT).Very Low Frequency Method is one of Geophysics methods that use magnetic com-ponent of electromagnetics field wich is caused by radio broadcaster use Frequency 15-30 kHz. VLF Method applied to know characteristic around the minimum geomagnetic anomaly in the form result of current density image which able to show conductive or itâ€™s not an measurement area.This VLF Acquisition conducted to know the zona of conductive layer as long as 2500 metres from south to north pass the minimum geomagnetic anomaly. The tilt data processing is done use Moving Average method and Linear filter with use Matlab 6.1 . The Result of data processing show the contour of current density with depth/space = 8 or maximum deep is 160 metres with conductive area is spread near the minimum geomagnetic anomaly which is estimated much water